A cooperative target-fencing protocol of multiple vehicles. (September 2019) - Chen, Zhiyong
Abstract: A class of cooperative controllers is designed for a group of autonomous vehicles, using the relative positions between geographical neighbors and a specified target. The controller is equipped with three components: attractive component that drives each vehicle towards the target, repulsive component between adjacent vehicles, and rotation component for neighbored vehicles aligned with the target in a straight line. It is proved that the vehicles with the proposed autonomous controller can asymptotically fence a specified target to their convex hull. Meanwhile, the vehicles do not collide and they are not stuck in a singleton formation.